Retro Marketing – A Power of Nostalgia Which Works Among the Audience - Holotová, Mária; Kádeková, Zdenka; Košičiarová, Ingrida (Communication Today, 2020)
The nostalgia behind historic brands and trends is definitely making large waves in the consumer market. With a good idea, even the most modern company can engage in a retro revolution. Studies suggest that nostalgia encourages consumers to spend their money by promising an immediate return in the form of happy memories. The reason why retro marketing has become increasingly popular in recent years is the linking of the brand and the customer at a deeper, emotional level. Brands, especially those that served as milestones of a particular generation should design a heart-warming nostalgia marketing strategy to make a product appeal to a target market. Lots of organisations are falling back into retro marketing as a strategy to increase sales and they are raking in profits. The aim of the study is to present the relevance and possibilities of using ‘retro trend’ in marketing communication and to point out the power of nostalgia between different age generations. In this scholarly article, examples of retro-communication of global and local food brands are presented. The current marketing situation is described by outcomes of similar studies provided by professional agencies, and economic benefits concerning retro communication campaigns are also provided. In order to meet the objectives of the study, our own research was conducted (530 respondents from the Slovak Republic belonging to Generations Z, Millennials, Generation X and Baby Boomers were involved in the research). The research findings confirmed the significance of retro marketing communication and its impact on consumers attitudes between the abovementioned age generations. For statistical processing of the results, we used the Kruskal-Wallis Test, Dunn’s Test of Contrasts, Fisher’s Exact Test and Chi-Square Test of Independence.